Dinâmica espacial da produção de mandioca no Paraná, Brasil - Talita Pijus Ponce; Marina Ronchesel Ribeiro; Tiago Santos Telles (Confins)
Grown in more than 100 countries, cassava is a rustic plant that is not very demanding in soil fertility. An important food source, cassava has great relevance in food security in tropical regions. Brazil is the fourth largest cassava producer in the world. Cassava production occurs in all states of the country. This study aimed to verify the spatial dynamics of cassava production in Paraná, identifying the microregions specialized in the activity and the evolution and spatial distribution of production, from 1999 to 2018. For this, the locational quotient (QL) methodology was applied, principal component analysis (ACP) and cluster analysis were carried out. The QL results, subdivided into periods of 5 years, denote changes in the spatial dynamics of cassava production. There was a reduction in the number of microregions specialized in cassava production, from 11 in the period from 1999 to 2003, to 9 in the period from 2014 to 2018. Two main components were identified that explained 74% of the total variability of the data, the first formed by micro-regions with a high level of specialization and high participation in rural credit, the second for micro-regions with high productivity. By the degree of similarity, four groups were defined, showing the heterogeneity between the regions that stand out in cassava production. There was a transformation in cassava production systems, related to the technification of production systems. The results reinforce the importance of investments in technology in the development of the cassava production chain.